Family care in chronic obstructive pulmonary disease: what happens when the carer is a man?. Issue 4 (13th October 2015) - Figueiredo, Daniela; Jácome, Cristina; Gabriel, Raquel; Marques, Alda
Abstract : Chronic obstructive pulmonary disease (COPD) is a major cause of disability, morbidity and mortality in old age, representing a significant burden for family carers. However, knowledge regarding the specific issues faced by men in the COPD caregiving role is nonexistent. This study explored the experience of husbands and sons providing care to a family member with moderate‐to‐severe COPD. A cross‐sectional qualitative study using in‐depth, semi‐structured individual interviews was conducted with twelve men carers: seven husbands with a mean age of 70.9 ± 8.8 years and five sons with a mean age of 43.4 ± 10.5 years. The interviews were analysed for recurrent themes using thematic analysis. Main findings suggest that men are committed and dedicated carers; however, differences between husbands and sons related to 'meaning', 'challenges and constraints', 'fears and concerns about the future', 'needs' and 'positive aspects' have emerged. These differences reflect relationship and generational differences and are of relevance when planning adequate community support interventions.